Modelling and interpretation of gas detection using remote laser pointers - Hodgkinson, Jane; van Well, Ben; Padgett, Miles; Pride, Russ D. (Elsevier, 2006)
We have developed a quantitative model of the performance of laser pointer style gas leak detectors, which are based on remote detection of backscattered radiation. The model incorporates instrumental noise limits, the reflectivity of the target background surface and a mathematical description of gas leak dispersion in constant wind speed and turbulence conditions. We have investigated optimum instrument performance and limits of detection in simulated leak detection situations. We predict that the optimum height for instruments is at eye level or above, giving an operating range of 10 m or more for most background surfaces, in wind speeds of up to 2.5 m s−1. For ground based leak sources, we find laser pointer measurements are dominated by gas concentrations over a short distance close to the target surface, making their readings intuitive to end users in most cases. This finding is consistent with the results of field trials.
Special Issue: 5th International Conference on Tunable Diode Laser Spectroscopy, 11-15 July 2005, Florence, Italy
Keywords: Gas; Methane; Leak; Detection; Dispersion